Clusters of injuries and chronic health conditions and their changes between baseline and follow-up of the kindergarten cohort - Ou, L; Chen, J (My University, 2007)
This document features slides from a presentation on childhood injuries and chronic illness. Based on data from 'Growing Up in Australia: the Longitudinal Study of Australian Children' (LSAC), the authors asked whether there were any underlying distinctive groups behind chronic health conditions and injuries, and, if so, whether there are relationships between these groups, whether the groups change over time, and whether there are predictors. The slides outline baseline measures of injuries and ongoing health conditions, latent class analysis, methodology, and predictive variables for the groups with the worst and the best health.
Keywords: Health; Health -- Injury; Health and wellbeing; Health; Injury; Health and wellbeing